Ethical Da'wah and Leadership: Raja Ali Haji‘s Philosophical Perspectives on Moral Governance - Hassan Palawa, Alimuddin; Nuh, Zulkifli M; Hanafi, Imam; Masduki, Moh (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines Raja Ali Haji's thoughts on Islamic leadership based on da'wah ethics by highlighting his works, such as Gurindam Dua Belas, Thamarāt al-Muhimmah, and Tuhfat al-Nafis. Through a historical approach and textual analysis, this article explores how values such as reason, knowledge, politeness, exemplary, and deliberation are basic principles in building an ethical, communicative, and spiritual leadership model. The article finds that the ethics of da'wah, according to Raja Ali Haji is not only individual and normative but also has a strong socio-political dimension, which is in line with the theory of political da'wah and the concept of civil Islam in the contemporary context. Raja Ali Haji's thinking can be used as a normative and pedagogical framework in the formation of Muslim leaders who are responsive to the times, fair in policy, and communicative in dealing with the plurality of society. The article also highlights the challenges in realizing civilized da'wah in the era of social media and populist politics and recommends integrating da'wah ethical values into education and public leadership practices in Indonesia.